CULINARY AS A REPRESENTATION OF NATIONALISM IN THE NOVEL PULANG BY LEILA S. CHUDORI: MAKANAN SEBAGAI REPRESENTASI NASIONALISME DALAM NOVEL PULANG KARYA LEILA S. CHUDORI - Jung Ju Roh; M Yoesoef; Turita Indah Setyani (Jurnal Kata, 2022)
This study uses the novel Pulang by Leila S. Chudori with the aim of dismantling the representation of nationalism depicted through food in literary works. This study uses a qualitative descriptive research method with a gastrocritical approach, a research paradigm to analyze culinary literature and semiotics to uncover signs in the text. The results of this study reveal that there are 2 types of food found in the narrative of the novel, namely spices and food. Both types of food are symbols as representations of nationalism described by the characters. Then, the fluid fabric in the narrative structure of this novel presents ideological issues related to a sense of ownership, love for the homeland, and an identity that is maintained by the exiled characters and other characters through food.